1970
DOI: 10.1104/pp.45.4.401
|View full text |Cite
|
Sign up to set email alerts
|

The Ribosomes of Pear Fruit

Abstract: Maceration at liquid nitrogen temperatures, use of polyvinylpyrrolidone, and careful pH control are essential to the isolation of ribosomes and polysomes from deciduous fruit tissue. Characteristics of the ribosomes and constituent RNA are described. Superimposed intracellular radiation injury stimulates the synthesis of new ribosomes and underscores a major transition in the dynamics of the ribosomal system coincident with the climacteric rise.Fruits and leaves have often been used as sources of tissue commit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
2
0

Year Published

1973
1973
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(5 citation statements)
references
References 34 publications
3
2
0
Order By: Relevance
“…These results suggest that the continuous stimulation in ethylene production induced by wounding is transcriptiondependent and that irradiation, through its well-known action on DNA, impairs this stimulation. Such interpretation is in accordance with previous results showing an impairment of ribosomal synthesis with possible recovery in pear fruits (12) and damage and repair processes of proteins in tomato fruits ( 1 8).…”
Section: Efe Radiosensitivitysupporting
confidence: 93%
“…These results suggest that the continuous stimulation in ethylene production induced by wounding is transcriptiondependent and that irradiation, through its well-known action on DNA, impairs this stimulation. Such interpretation is in accordance with previous results showing an impairment of ribosomal synthesis with possible recovery in pear fruits (12) and damage and repair processes of proteins in tomato fruits ( 1 8).…”
Section: Efe Radiosensitivitysupporting
confidence: 93%
“…This increase in ribosomes noted at the beginning of ripening is in good accordance with the increase in ribosomal synthesis found in avocado (16), figs (12), and pear fruit (9,17) at the beginning of the climacteric. Yet, the increase in polyribosomes noted with progressive ripening of our pear fruit is contrary to these studies.…”
Section: Resultssupporting
confidence: 87%
“…Moreover, we found that, during the ripening of tomato fruit, the levels of both SnoR12.1 and SnoU24a maximized at the unripe, green stage of the fruit, declining thereafter upon ripening; during the progression of ripening, the decline in SnoR12.1 transcripts was slower than the rapid decline in SnoU24a transcripts [11]. Interestingly, an overall decline in protein synthesis accompanied by a decline in the de novo ribosome and rRNA synthesis was also previously observed in tomato fruit upon ripening [14][15][16].…”
Section: Introductionsupporting
confidence: 63%